Image Guidance in Ventricular Cerebrospinal Fluid Shunt Catheter Placement: A Systematic Review and Meta-Analysis. Issue 3 (19th June 2015) - Nesvick, Cody L.; Khan, Nickalus R.; Mehta, Gautam U.; Klimo, Paul
Abstract: BACKGROUND: Ventricular shunt placement for treating hydrocephalus is one of the most common neurosurgical procedures. The rate of shunt failure, however, has not appreciably changed with time. OBJECTIVE: To investigate whether intraoperative image guidance using ultrasound or stereotaxy contributes to accurate shunt catheter placement and survival. METHODS: We performed a systematic literature review using PubMed and MEDLINE databases for studies that use ultrasound and frameless stereotaxy for ventricular catheter placement for hydrocephalus. All articles assessed the accuracy of catheter tip placement and/or overall shunt survival, and the rate of accurate shunt catheter placement, the overall failure rate, and the average time to shunt failure were extracted for analysis. RESULTS: Although each modality (ultrasound/stereotaxy) did not increase catheter placement accuracy, a combined random-effects meta-analysis of 738 catheters (136 guided by ultrasound, 168 guided by frameless stereotaxy, and 434 freehand) demonstrated a weak benefit of image guidance (risk ratio: 1.19, 95% confidence interval: 1.02-1.39, P = .02), but this result was limited by considerable heterogeneity among studies (I 2 = 86%, P < .001 by Cochrane's Q test). A meta-analysis could not be performed for shunt survival due to heterogeneity in data reporting. CONCLUSION: Although image guidance offers a promising solution to lower the risk of inaccurate catheter placement, which could lead to lower premature failure of ventricular shunts, our review demonstrated that there is not yet a clear benefit of these technologies. Current literature is limited to case series and cohort studies, and significant between-study heterogeneity in methodology and reporting currently limits a higher order analysis.